Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

Pd loaded bismuth ferrite: a versatile perovskite for dual applications as acetone gas sensor and photocatalytic dye degradation of malachite green - Ghadage, Pandurang; Kodam, Pavan; Nadargi, Digambar; Patil, Suraj; Tamboli, Mohaseen; Bhandari, Nagesh; Mulla, Imtiaz; Park, Chinho; Suryavanshi, Sharad (Ceramics International, 2023)
Herein we report the palladium loaded bismuth ferrite for its bidirectional application as acetone gas sensor and photocatalytic dye degradation of malachite green. The motivation for loading Pd on bismuth ferrite (BFO) is due to its fascinating catalytic redox reactions causing faster adsorption and desorption of the oxygen molecules over the metal oxide. The planned perovskites were developed via surfactant assisted sol-gel auto-combustion route, and characterized their physico-chemical properties using XRD, SEM, TEM, HRTEM, EDAX, XPS and BET. The developed BFO showed the best selectivity towards acetone, whose response was 69% at 300 degrees C operating temperature for 500 ppm gas concentration. By tuning the surface area and catalytic behavior using CTAB and Pd loading, respectively, the enhancement in the gas response properties of BFO was achieved to 95% with the response and recovery time of 75 s and 104 s. The 1 wt% Pd loaded BFO showed the highest response (95%) in comparison to rest of the Pd loadings (0.5, 1.5 and 2.0 wt%). Moreover, the sunlight driven photocatalytic dye degradation of malachite green is carried out at 1 h exposure time. Here as well, 1 wt% Pd loaded BFO exhibited the maximum dye degradation efficiency of 51%. The results of this study demonstrate the developed perovskites have a significant potential for the use in dual applications such as acetone gas sensor and MG photocatalysis.
Keywords: Acetone sensor; Bismuth ferrite; Palladium loading; Photo dye -degradation